PENGARUH FAKTOR MAKROEKONOMI DAN LIKUIDITAS TERHADAP YIELD CURVE OBLIGASI PEMERINTAH INDONESIA - Pardomuan Sihombing; Hary Saputra Sundoro (Media Ekonomi, 2017)
The purpose of this study is to estimate the movement of the required yield curve as a reference to predict market expectations. The movement of the yield curve is caused by macroeconomics such as the BI rate, inflation, the money supply, the growth of the production index, foreign exchange reserves and foreign investor ownership. This study uses the help of a VAR (Vector Auto Regression) analysis tool or VECM (Vector Error Correction Model) using data from 2007:2-2016:3. The results of this study indicate that all variables both macroeconomic variables and liquidity variables provide a response to the yield curve of government bonds to long-term. In addition, this paper also explains that all variables both in macroeconomics and liquidity variables only have a small contribution to the yield curve but precisely the variable that makes the biggest contribution is the yield curve